High-Resolution 3D Reconstruction of Human Oocytes Using Focused Ion Beam Scanning Electron Microscopy - Trebichalská, Zuzana; Javůrek, Jakub; Tatíčková, Martina; Kyjovská, Drahomíra; Kloudová, Soňa; Otevřel, Pavel; Hampl, Aleš; Holubcová, Zuzana (Frontiers in Cell and Developmental Biology, 2021)
The egg plays a pivotal role in the reproduction of our species. Nevertheless, its fundamental biology remains elusive. Transmission electron microscopy is traditionally used to inspect the ultrastructure of female gametes. However, two-dimensional micrographs contain only fragmentary information about the spatial organization of the complex oocyte cytoplasm. Here, we employed the Focused Ion Beam Scanning Electron Microscopy (FIB-SEM) to explore human oocyte intracellular morphology in three dimensions (3D). Volume reconstruction of generated image stacks provided an unprecedented view of ooplasmic architecture. Organelle distribution patterns observed in nine donor oocytes, representing three maturational stages, documented structural changes underlying the process by which the egg acquires developmental competence. 3D image segmentation was performed to extract information about distinct organelle populations, and the following quantitative analysis revealed that the mitochondrion occupies ∼ 4.26% of the maturing oocyte cytoplasm. In summary, this proof-of-concept study demonstrates the potential of large volume electron microscopy to study rare samples of delicate female gametes and paves the way for applying the FIB-SEM technique in human oocyte research.